Potensi Ekstrak Kangkung sebagai Biofungisida untuk Mengendalikan Penyakit Busuk Buah Fusarium pada Tomat - Bonny Poernomo Wahyu Soekarno; Surono .; Eva Marhaenis (Jurnal Fitopatologi Indonesia, 2012)
One of the important pathogens on tomato is Fusarium sp. causing wilt and fruit rot. This study aims to investigate the potency of water spinach (Ipomea aquatica) as a biofungicide for inhibiting growth and development of tomato fruit rot caused by Fusarium sp. This study showed inhibiting ability of  I. aquatica stem extract to Fusarium sp. growth ranges from 3.40% to 8.67%, while inhibiting ability of leaves extract can reach 3.40% to 45.55%. Resistance induction test showed that in vitro treatment of I. aquatica leaves extract 20% can lengthen incubation time of Fusarium fruit rot compared to positive and negative control. Leaves extract of I. aquatica 20% is potential as biofungicide.Key words: biofungicide, Fusarium sp., Ipomea aquatica